Eksplorasi dan Keanekaragaman Jamur Makroskopis di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Gunung Bromo Karanganyar sebelah Timur - Syihab, Naufal Khoirus; Saputra, Yuanda Eka; Kusumawardani, Agita Asri; Setyaningsih, Endang (Journal of Natural Sciences, 2026)
Macrofungi are important components of forest ecosystems that function as decomposers in the breakdown of organic matter. Information on fungal diversity in the Forest Area with Special Purpose (KHDTK) Gunung Bromo Karanganyar, particularly on the eastern lower slope, remains limited. This study aimed to explore and identify macrofungi in this area. The research used an exploratory method through a free-roaming field survey along the first ±5 km of the eastern lower slope. Each fungal sample encountered was directly observed at the site of discovery and identified based on the macroscopic morphological characteristics of the fruiting bodies and their growth substrates. The results recorded 9 species of macrofungi belonging to two divisions, namely Basidiomycota (7 species; 77.8%) and Ascomycota (2 species; 22.2%). Approximately 77.8% of the species were found growing on decaying wood, with Schizophyllum commune showing the highest occurrence frequency. These findings indicate that the macrofungal community is dominated by saprotrophic fungi, which play an important role in organic matter decomposition and nutrient cycling in forest ecosystems.